RICE-HUSK BIOCHAR AND TRICHODERMA FORTIFICATION MODULATE THE CHEMICAL AND MICROBIOLOGICAL PROFILES OF ORGANIC-WASTE LIQUID FERTILIZER - Ansyori; Herfandi Lamdo; Yanto (RADJA PUBLIKA, 2026)
Liquid organic fertilizer (LOF) derived from mixed organic residues may promote nutrient circularity; however, its chemical quality and microbial viability depend on formulation and fermentation conditions. This study assessed the effects of rice-husk biochar and Trichoderma spp. fortification on LOF produced from banana peel, pineapple peel, rabbit urine, and molasses in a passively aerated stacked-bucket system. A randomized complete block design included four treatments with four replicates: unfortified LOF (P1), Trichoderma alone (P2), 1% w/v biochar (P3), and biochar plus Trichoderma (P4). Chemical variables were analyzed by ANOVA followed by Tukey's HSD test at 5%, whereas microbial and metal data were interpreted descriptively. Fortification did not affect pH (7.20–7.22). P3 had the highest organic C (0.58%) and C/N ratio (5.92), whereas P4 had the highest total N (0.12%), P (0.22%), and K (0.62%). P2 had the highest total fungal count (7.2 × 10⁵ CFU mL⁻¹) and recoverable Trichoderma population (6.5 × 10⁵ CFU mL⁻¹); corresponding values in P4 were 3.8 × 10⁵ and 3.5 × 10⁵ CFU mL⁻¹. Co-fortification improved macronutrient profiles but did not maximize Trichoderma recovery from the liquid fraction. Further optimization and plant-based efficacy testing are required.